Conserving agricultural biodiversity in situ : (International Plant Genetic Resources Institute (IPGRI), 2000)
The report reflected the amount and distribution of genetic diversity maintained by farmers; the process used to maintain genetic diversity on-farm; the holders who maintain the diversity, the factors that influence farmers, etc